Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 6 - Cumulative Review: 45

Answer

=($x^{2}$+3)($x^{2}$+2)

Work Step by Step

$x^{4}$+5$x^{2}$+6= =$x^{4}$+2$x^{2}$+3$x^{2}$+6= =$x^{2}$($x^{2}$+2)+3($x^{2}$+2)= =($x^{2}$+3)($x^{2}$+2)
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.